2016
DOI: 10.3102/0002831216667478
|View full text |Cite
|
Sign up to set email alerts
|

School Organizational Contexts, Teacher Turnover, and Student Achievement

Abstract: We study the relationship between school organizational contexts, teacher turnover, and student achievement in New York City (NYC) middle schools. Using factor analysis, we construct measures of four distinct dimensions of school climate captured on the annual NYC School Survey. We identify credible estimates by isolating variation in organizational contexts within schools over time. We find that improvements in school leadership especially, as well as in academic expectations, teacher relationships, and schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
218
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 228 publications
(246 citation statements)
references
References 61 publications
(74 reference statements)
19
218
1
8
Order By: Relevance
“…To examine organizational antecedents, literature explored the role of the leaders in organizations. For example, the influence of the leader on selfefficacy, perceptions of the leader's expectations and role, providing a supportive environment, clarifying the organization's vision and goals, providing a safe environment, and developing and sustaining a positive culture (Darling-Hammond, 2003;Hirsch, Emerick, Church, & Fuller, 2007;Kraft et al, 2016;Loeb et al, 2005;Pogodzinski et al, 2012). The outcome of the study suggested that positive organizational environments enhanced EE (Shuck & Wollard, 2010).…”
Section: Antecedents To Employee Engagementmentioning
confidence: 94%
See 4 more Smart Citations
“…To examine organizational antecedents, literature explored the role of the leaders in organizations. For example, the influence of the leader on selfefficacy, perceptions of the leader's expectations and role, providing a supportive environment, clarifying the organization's vision and goals, providing a safe environment, and developing and sustaining a positive culture (Darling-Hammond, 2003;Hirsch, Emerick, Church, & Fuller, 2007;Kraft et al, 2016;Loeb et al, 2005;Pogodzinski et al, 2012). The outcome of the study suggested that positive organizational environments enhanced EE (Shuck & Wollard, 2010).…”
Section: Antecedents To Employee Engagementmentioning
confidence: 94%
“…Despite the negative statistics that illustrate a significant teacher attrition problem in low-performing schools, there is evidence that there are some veteran teachers who remain in low-performing schools for extended periods beyond the average five years (Clotfelter et al, 2004). Related literature supported that retaining highly effective veteran teachers would help schools to be more effective in the turnaround effort (Ingersoll & Merrill, 2013;Ingersoll et al, 2014;Kraft et al, 2016). However, only one study has been identified that examined factors that influenced veteran teachers to remain in the teaching profession.…”
Section: Chapter II Literature Reviewmentioning
confidence: 96%
See 3 more Smart Citations